Delirium and its consequences in the specialized palliative care unit: Validation of the Korean version of Memorial Delirium Assessment Scale. Issue 1 (8th November 2018) - Kang, Beodeul; Kim, Yu Jung; Suh, Seung Wan; Son, Kyung‐Lak; Ahn, Grace S.; Park, Hye Youn
Abstract: Objectives: Delirium is highly prevalent in patients with advanced cancer. This study aimed to investigate delirium rates and potential associated factors such as mortality in patients admitted to an acute palliative care unit (APCU). Our second aim was to validate the Korean version of the Memorial Delirium Assessment Scale (K‐MDAS). Methods: A total of 102 patients with advanced cancer, and who were admitted to the APCU, were assessed. Demographic data were collected alongside clinical diagnosis, Eastern Cooperative Oncology Group (ECOG) performance status, clinical symptoms according to the Edmonton Symptom Assessment System, history of smoking, alcohol use, hypnotic use, and daily dose of morphine were collected. The Confusion Assessment Method, the Delirium Rating Scale‐Revised 98, and the K‐MDAS were measured at admission and 1 week later. Results: Twenty‐four patients (23.52%) were diagnosed with delirium, and associated factors were old age ( P  = 0.007), higher ECOG ( P  = 0.011), and drowsiness ( P  < 0.001). The presence of delirium was an independent predictor of 1‐month mortality; male gender, higher body mass index, and hypnotic use were also related to 1‐month mortality. The K‐MDAS had reliable internal consistency (α = 0.942) and showed sensitivity of 0.958 and specificity of 0.921 at the optimal cutoff score for diagnosing delirium of 9. Conclusions: Delirium was prevalent in patients admitted to the APCU and was associated with 1‐month mortality. The K‐MDAS showed acceptable reliability and validity and can be used to screen for delirium in a palliative care setting.